‘AZIMAHDANRUKHSHAH SUATU KAJIAN DALAM HUKUM ISLAM - Sulastri Caniago (JURIS (Jurnal Ilmiah Syariah), 2018)
Talisman (‘Azimah) and dispensation (Rukhshah) were a study in Islamic law that brought the principles of law (general and optional principles). In normal condition, Talisman (‘Azimah) could be done, and dispensation (Rukhshah) could be done optionally when condition did not support it. The concept of Talisman (‘Azimah) and dispensation (Rukhshah) presented that Islamic law was flexible and dinamic based on one’s condition. Therefore, all of Allah’s command to do or to do not do something could be done. This was in line with the demand of developed era.